Comparative analysis of volatile and phenolic composition of alternative wood chips from cherry, acacia and oak for potential use in enology. - Jordão, António M. (2017)
The aim of present work was to investigate the phenolic and volatile composition of cherry, acacia, and oak (from different species) wood chips. By the use of HPLC-DAD 18 different phenolic compounds were detected and quantified while for volatile composition, 33 different compounds were detected by GC-MS. In general, wood samples from oak species showed the higher number of phenolic compounds detected, while cherry wood samples showed the lowest levels. In addition, some individual phenolic compounds were detected, specifically in some wood samples, such as robinetin in acacia woods and naringenin in cherry wood. For volatile composition, cherry wood chips samples showed the lowest volatile composition followed by increasing order by acacia, French, Portuguese and American wood chip samples. Oak wood chip samples from American species showed the highest volatile content, as a result of high levels of several specific compounds (furfural, 5-methyfurfural, β-methyl-γ-octalactones, guaiacol, vanillin and siringaldehyde).